2016
DOI: 10.1103/physrevb.93.161113
|View full text |Cite
|
Sign up to set email alerts
|

Electronic correlations in the ferroelectric metallic state ofLiOsO3

Abstract: LiOsO3 has been recently identified as the first unambiguous "ferroelectric metal", experimentally realizing a prediction from 1965 by Anderson and Blount. In this work, we investigate the metallic state in LiOsO3 by means of infrared spectroscopy supplemented by Density Functional Theory and Dynamical Mean Field Theory calculations. Our measurements and theoretical calculations clearly show that LiOsO3 is a very bad metal with a small quasiparticle weight, close to a Mott-Hubbard localization transition. The … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
38
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 37 publications
4
38
1
Order By: Relevance
“…Such materials should be very hard to obtain because the free carriers screen the long-range coulomb interaction, and therefore weaken the ferroelectric polar distortion. Nevertheless, not long ago, an unambiguous experimental evidence of ferroelectric-like structure transition in metallic material LiOsO3 has reattracted much attention on the metals with non-centrosymmetric structures, which was observed in low temperature below 150 K. [2][3][4][5][6][7][8] Yet, they remain challenging to discover. 8,9 So far no room temperature candidate for the coexistence of polar distortion and metallicity has been obtained.…”
mentioning
confidence: 99%
“…Such materials should be very hard to obtain because the free carriers screen the long-range coulomb interaction, and therefore weaken the ferroelectric polar distortion. Nevertheless, not long ago, an unambiguous experimental evidence of ferroelectric-like structure transition in metallic material LiOsO3 has reattracted much attention on the metals with non-centrosymmetric structures, which was observed in low temperature below 150 K. [2][3][4][5][6][7][8] Yet, they remain challenging to discover. 8,9 So far no room temperature candidate for the coexistence of polar distortion and metallicity has been obtained.…”
mentioning
confidence: 99%
“…In ref. , ( U = 2.3 eV, J H = 0.345 eV) are adopted in the LDA + DMFT calculation which can lead to a large local moment (≈2.5 μ B /Os) . Then a crucial question is what are the proper values of U (and J H ) for LiOsO 3 , which are decisive for the ground state in the first‐principles calculations.…”
Section: Structural Parameters Of Lioso3 and Naoso3 Calculated Using mentioning
confidence: 99%
“…[7] had formula Li 0.98 OsO 3 , it has been argued that the Li-vacancy level may need to be closer to a Li 0.94 OsO 3 composition in order to allow the ferroelectric metallic phase to exist [14]. It has also been suggested that strong electron-electron correlations bring LiOsO 3 close to a Mott-Hubbard transition, but these are not strong enough to produce insulating behaviour [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In high-defect structures, it is possible that magnetism may be destroyed entirely. In the case that the ferroelectric transition were to be caused by band hybridization, however, the AFM state is disfavoured as it would result in an insulating ground state instead of a metallic one [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation